Pengaruh Formulasi Tepung Kacang Hijau Dan Tepung Wortel Terhadap Kadar Air Dan Daya Terima Cookies - Diana Loveitasari; Arya Ulilalbab; Cucuk Suprihartini; Rizka Mar’atus Sholichah (Master Program of Food Science and Technology, Faculty of Agricultural Technology, Udayana University, 2021)
Carrot and mung bean cookies was the kind of food that made from rice flour, carrot flour, mung bean flour, powdered milk, egg, butter, maizena, and sugar. This kind of product were made from carrot and mung bean that converted into powdered by adding formulation P1 that approximately 16.55% of mung bean powder’s, and 15% carrot flour, continued with formulation P2 that consist of 11.55% of mung bean powder, and 20% of carrot flours. This research regarded as experimental research. This research is to discover the effect of the formulation of mung bean flour and carrot flour towards cookies’s water content and acceptability. This research was conducted on February 2019 at food technology and chemical laboratory Akademi Gizi Karya Husada Kediri. This research was done by using hedonic scale test to acceptability and thermografimetri test to discover water content. Acceptability were done by using friedman statistical analysis test and the result is sig. = 0,05, in addition the water content were using One way anova with sig. = 0,01 using SPSS 16.0. If H0 were rejected so it will be continued with Duncan’s test. The result shown that there were significance improvement towards the colour (sig. 0.00), smell (0.01), and taste (0.02) in the cookies due the adding of Mung bean flour and carrot flour. However, it did not influence the water content (0.35), and the texture (sig, 0.89). The best cookies were made from colour absorption and smell which is control, on the other hand the texture and the taste from formulation 2. The lowest water content were located on control product (3.5%). This research has not been conducted to discover the expiration date test. The following researches are encouraged to discover the expiration date test, and the product innovation by adding natural ingredients towards the cookies.